The Influence of Perceived Organizational Support on Talent Management and Job Performance - Jimoh, Adams Lukman (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The purpose of this present study stems from the fact that weak talent management in Nigerian private universities has contributed tremendously to the poor performance of the academic employees of the institutions, which is severely affecting the country's university education system and causing them to decline. The study employed a descriptive research survey to analysis the demography respondents of the study while partial least square structural equation model (PLS-SEM) was used to test the formulated hypotheses of the study. The population was 1,249 academic employees of the selected private universities in Nigeria, while 355 self administered questionnaires were administered, fully completed and returned. According to the findings, talent management has a significant impact on job performance, and POS mediates the relationship between talent management and job performance. Based on previous research, this study contributes to the field of study both practically and theoretically by adding to the body of knowledge by providing insight into the mediating position of POS on talent management and job performance in the Nigerian private university system. It also helps to identify the need for talent management in the Nigerian university system, likewise, providing empirical solutions to the performance challenges experienced by private universities in Nigeria. Keywords: job performance, pos, talent attraction, talent management, talent retention